2021
DOI: 10.7717/peerj.12579
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical models of acute liver failure: a comprehensive review

Abstract: Acute liver failure is marked by the rapid deterioration of liver function in a previously well patient over period of days to weeks. Though relatively rare, it is associated with high morbidity and mortality. This makes it a challenging disease to study clinically, necessitating reliance on preclinical models as means to explore pathophysiology and novel therapies. Preclinical models of acute liver failure are artificial by nature, and generally fall into one of three categories: surgical, pharmacologic or im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 213 publications
(245 reference statements)
0
10
0
Order By: Relevance
“…Hepatotoxins have been extensively used in the development of animal models with ALF ( 59 ). d -Gal is commonly used as the pharmacological agent for inducing ALF in preclinical models.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatotoxins have been extensively used in the development of animal models with ALF ( 59 ). d -Gal is commonly used as the pharmacological agent for inducing ALF in preclinical models.…”
Section: Methodsmentioning
confidence: 99%
“…d -Gal is commonly used as the pharmacological agent for inducing ALF in preclinical models. The literatures reported that rats are known to be sensitive to d -Gal for inducing hepatic failure ( 59 , 60 ). Therefore, rats were considered as the animal model to develop ALF in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Most ALF models are artificial systems, which include surgical, pharmacological or immunogenic models. Immunogenic models include various viral hepatitis models (8). One of them is Lagovirus europaeus infection, which causes Rabbit Hemorrhagic Disease (RHD).…”
Section: Rabbit Model Of Acute Liver Failurementioning
confidence: 99%
“…However, in the case of clinical entities such as ALF, which are difficult to study clinically due to the rarity of occurrence and high mortality, studies based on animal models are crucial. They enable, above all, a better understanding of pathophysiology, but also the development of potential therapeutic methods (8). One of the proposed animal models of ALF is infection of rabbits (Oryctolagus cuniculus) with Lagovirus (L.) europaeus virus, which causes severe Rabbit Hemorrhagic Disease (RHD) (9).…”
mentioning
confidence: 99%
“…CCL4 is one of the most commonly used agents to induce chronic and acute liver failure in experimental animals at doses of 0.5–2.5 mL/kg. Other pharmacological models of liver failure such as acetaminophen can be used, but rats are less sensitive to it`s toxic effects even at higher doses (300–1000 mg/kg IP) [ 9 ]. When CCl 4 gets into the liver, it acts as a xenobiotic and converted into free radicals CCl 3 and CCl 3 O 2 by the P-450 monooxygenase-dependent microsome system and causes liver damage through membrane lipid peroxidation [ 10 ].…”
Section: Introductionmentioning
confidence: 99%